Volume of containers and types of seeds for jabuticabeira seedling production - Vendruscolo, Eduardo Pradi; Campos, Luiz Fernandes Cardoso; Seleguini, Alexsander (Scientia Agraria Paranaensis, 2017)
<span style="font-family: 'Helvetica',sans-serif; font-size: 10pt; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The jabuticabeira is a native species of Brazil and has potential for the production of cosmetics, processed foods and fresh consumption. However, little research has been conducted on the production system, resulting in shortage of information about the species. In this sense, the objective was to define the best conditions for the production of jabuticabeira seedlings by the use of different containers volumes and seed types. In a completely randomized design with factorial 3 x 3 and four replications, partially pulped seeds, not pulped seeds and seeds from fruits collected on the ground were sown in plastic tubes of three volumes (50, 100 and 300 cm3). For each treatment were evaluated parameters related to the emergence and biometry of plants. There was a significant response of all variables, except for the average time of emergency and diameter at the base of the neck. It was observed that with the use of tubes 300 cm3 was better development of seedlings, while the use of seed not pulped and partially pulped provided the best results in the emergence and development of plants, respectively. Thus, for the experimental conditions, large and medium combined with tubes partially pulped pulp or seeds can be used for the production of jabuticabeira "pingo-de-mel".